Impact of COVID-19 and Lockdown on Religious Tourism Business: A Study of Changunarayan, Bhaktapur - Khadka, Bimal Kumar (GS WOW: Wisdom of Worthy Research Journal, 2025)
Religious tourism is a significant contributor to Nepal’s tourism industry, attracting large numbers of visitors each year. However, the COVID-19 pandemic and lockdowns have severely impacted the livelihoods of those who depend on this sector, particularly small entrepreneurs, local residents, and business owners in the Changunarayan temple area. This study assessed how these disruptions affected small traders, general store owners, and hotel operators, using a mixed-methods approach that included both qualitative and quantitative data from selected stakeholders. The findings reveal that most respondents rely on business as their main source of income and that tourist spending has not returned to pre-pandemic levels, with more than half of small business owners and a majority of hotel owners reporting reduced sales. Although Nepal’s tourism policies aim to improve living standards and diversify religious tourism, the study found these policies to be largely ineffective in addressing the specific needs of those whose livelihoods are closely tied to religious tourism. Overall, the research underscores the urgent need for more targeted and effective policy measures to support affected communities in the Changunarayan area.